2007
DOI: 10.1159/000112807
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Hypertension Is Associated with an Exacerbation of the Endothelial Damage in Preeclampsia

Abstract: Background: Non-dipping pattern of circadian blood pressure in preeclampsia is associated with an increased risk of cardiovascular disease. The pathogenetic mechanisms of this relationship are still unclear. We investigated whether non-dipping in preeclampsia could relate to endothelial activation or damage. Methods: Participants, 20 women with normal pregnancy (mean age 29.9 ± 5.7 years) and 31 women with preeclampsia (mean age 29.1 ± 5.1 years), un- derwent 24-hour ambulatory blood pressure monitoring. Plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…The prevalence of non-dipping observed in this cohort is greater than has been reported in several prominent observational studies of ABPM parameters, including 27.8% non-dipping rate reported in the PIUMA study among 959 individuals with ambulatory hypertension in Italy [47], and the 29.4% non-dipping rate reported within the IDACO cohort of 7458 individuals [48]. Non-dipping has been associated with adverse cardiovascular outcomes in a variety of European, American, and Asian cohorts [46, 49], including associations among pregnant women with pregnancy-induced hypertension [50] and increased risk of endothelial damage in preeclampsia [51]. Studies in the United States point to a potential racial and ethnic component of non-dipping patterns, with a larger prevalence of non-dipping SBP observed among African-Americans as compared to other racial groups [52, 53].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of non-dipping observed in this cohort is greater than has been reported in several prominent observational studies of ABPM parameters, including 27.8% non-dipping rate reported in the PIUMA study among 959 individuals with ambulatory hypertension in Italy [47], and the 29.4% non-dipping rate reported within the IDACO cohort of 7458 individuals [48]. Non-dipping has been associated with adverse cardiovascular outcomes in a variety of European, American, and Asian cohorts [46, 49], including associations among pregnant women with pregnancy-induced hypertension [50] and increased risk of endothelial damage in preeclampsia [51]. Studies in the United States point to a potential racial and ethnic component of non-dipping patterns, with a larger prevalence of non-dipping SBP observed among African-Americans as compared to other racial groups [52, 53].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, endothelial dysfunction is a key component in preeclampsia 15 and its adverse fetal and maternal outcomes. It has been suggested that administration of melatonin may lead to prevention of endothelial structural alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, vWf has attracted considerable attention in recent years as a marker of endothelial cell activation (Bergmann et al 1991) or injury (Brenner et al 1989). Significantly increased maternal plasma vWf levels have been reported in preeclampsia (Bouchlariotou et al 2008;Hulstein et al 2006;Nadar et al 2004;Peng et al 2010). Additionally, it has been reported that exposing the human umbilical vein to a hypoxic environment stimulates the release of vWf (Pinsky et al 1996;Trampont et al 2004).…”
Section: Introductionmentioning
confidence: 99%